A facile vacuum assisted synthesis of nanoparticle impregnated hydroxyapatite composites having excellent antimicrobial properties and biocompatibility. Issue 1 (January 2018) - Banerjee, Somtirtha; Bagchi, Biswajoy; Bhandary, Suman; Kool, Arpan; Amin Hoque, Nur; Thakur, Pradip; Das, Sukhen
Abstract: Porous nanocrystalline hydroxyapatite (HAp) pellet have been synthesized by co-precipitation method using cysteine as a chelating agent. The copper, gold, silver nanoparticles (NPs) were actively impregnated into the HAp pellets by absorption during vacuum filtration. NPs were characterized by UV–Visible spectroscopy and TEM. Impregnated pellets were characterized using X-ray diffraction (XRD) and Field emission scanning electron microscopy (FESEM) that confirmed the presence of nanocrystalline hydroxyapatite phase having interconnected granular porosity loaded with NPs both in the bulk and on the surface. All the NP loaded HAp showed strong antimicrobial activity against E. coli and S. aureus . Mechanism behind antimicrobial activity was found to be predominantly membrane damage and ROS (reactive oxygen species) mediated cell death generated from NPs. The release profile of NP loaded HAp pellets showed an initial rapid release within 6 h followed by a gradual release over a period of 24 h. Swelling index and release data indicated a sustained release of NPs from the pellets. Comparative cytotoxicity studies on human lung fibroblast (WI-38) showed gold (Au) nanoparticle impregnated HAp to be highly biocompatible compared to silver (Ag) and copper (Cu). The research findings clearly show that these NP loaded HAp holds great potential as a multifunctional therapeutic system for biomedical applications. Graphical abstract: Nanoparticle impregnated porous hydroxyapatite showing strong antimicrobial activity and biocompatibility.